The European charter for counteracting obesity: A late but important step towards action. Observations on the WHO-Europe ministerial conference, Istanbul, November 15-17, 2006 - Brug Johannes (BMC, 2007)
Abstract Background On November 15-17, 2006 the World Health Organization Regional Office for Europe organised a ministerial conference on counteracting obesity in the European region. Delegations from 48 countries met in Istanbul, Turkey. Observed by relevant nongovernmental organisations and expert temporary advisors, the European ministers adopted a charter on counteracting obesity. This charter states that countries within the European region should be able to show results in slowing down and stopping the obesity epidemic within the next 4-5 years, especially among children, and that the obesity prevalence trends should be reversed before 2015. To achieve this, the charter explicitly calls for action beyond health education: changes in the physical, political, informational and social environments are needed to facilitate a healthy energy balanced lifestyle. Discussion The fact that all member states of WHO-Europe have now explicitly agreed on an ecological approach to fighting the obesity epidemic with a timeline for visible results is important. However, the charter does not explicate specific enough and measurable objectives for improvement, nor the means needed to reach these. Summary The fact that all WHO-Europe member states have agreed on a charter that recognizes that counteracting obesity requires a multidisciplinary and ecological approach, with a timeline for improvements, is a late but important step forward for public health policy and practice across Europe. However, more specific tangible goals should now be set, the required means should be allocated, coordinated and immediate action should be implemented, and research to identify effective strategies should be encouraged and facilitated.